PELATIHAN & SHARING KNOWLEDGE: PENGENALAN FACE RECOGNITION TEKNOLOGI DALAM MENDETEKSI WAJAH - Tundo Tundo; Muhammad Rizqi Ramadhan; Andi Saidah (KAMI MENGABDI, 2026)
Community service activities related to Training & Knowledge Sharing: Introduction to Face Recognition Technology in Detecting Faces were held at SMAK Penabur 5 with the aim of improving students' understanding and skills in recognizing and utilizing face recognition technology as part of the development of artificial intelligence. In the rapidly developing digital era, the ability to understand biometric-based technology is important, especially in supporting aspects of security, identification, and technological innovation in everyday life. Through this knowledge sharing activity, participants were introduced to the basic concepts of face recognition, the working principles of systems in detecting and recognizing faces, and various methods used in digital image processing. The implementation methods included interactive lectures, case studies, and simple simulations of the use of application-based face recognition technology. The results of this activity showed an increase in students' understanding of the basic concepts of face recognition and awareness of the importance of using technology wisely, especially regarding privacy and data security issues. This activity is expected to be an initial provision for students in recognizing artificial intelligence-based technology and encourage their interest in developing skills in the field of information technology further, so that they are able to face future challenges more adaptively and critically